Effect of Magnesium and Antagonistic Bacteria Bacillus subtilis SM1 on Controlling Rigidoporus microporus NK6 in Vitro - Sangtong, Jutamas; Pengnoo, Ashara (YRU Journal of Science and Technology, 2023)
Nowadays, the exchangeable magnesium status, in rubber plantation areas in Southern Thailand, was mostly below the optimum range at 0.30 cmolc kg-1. Magnesium deficiency in soil has negative effects on plant growth process and sensitivity to plant disease infection by white root disease caused by Rigidoporus microporus. Biological control by using antagonistic bacteria such as Bacillus spp. has become an effective option for controlling plant disease. Therefore, this research aimed to study the effect of the antagonistic bacteria B. subtilis SM1 strain to prohibit R. microporus NK6 strain together with magnesium and its effect on growth of R. microporus.The result showed that, R. microporus NK6 strain was able to grow on potato dextrose agar (PDA) with magnesium but magnesium at concentrations of 0.3 and 0.5 cmolcL-1 occurred the change of mycelia morphology compared with no magnesium (control). B. subtilis SM1 strain was inhibited growth of R. microporus NK6 strain at 75.29% by dual culture test for the antagonistic evaluation. Consequently, using B. subtilis SM1 strain combined with magnesium at concentrations of 0.1 to 0.5 cmolcL-1 in PDA exhibited significantly reduced the growth of R. microporus NK6 strain compared with no magnesium (control).